A pilot study of traditional indoor biomass cooking and heating in rural Bhutan: gas and particle concentrations and emission rates. (16th March 2016) - Wangchuk, T.; He, C.; Knibbs, L. D.; Mazaheri, M.; Morawska, L.
Abstract: Although many studies have reported the health effects of biomass fuels in developing countries, relatively few have quantitatively characterized emissions from biomass stoves during cooking and heating. The aim of this pilot study was to characterize the emission characteristics of different biomass stoves in four rural houses in Bhutan during heating (metal chimney stove), rice cooking (traditional mud stove), fodder preparation (stone tripod stove), and liquor distillation (traditional mud stove). Three stage measurements (before, during, and after the activity had ceased) were conducted for PM2.5, particle number (PN), CO, and CO2 . When stoves were operated, the pollutant concentrations were significantly elevated above background levels, by an average of 40 and 18 times for PM2.5 and CO, respectively. Emission rates (mg/min) ranged from 1.07 × 10 2 (PM2.5 ) and 3.50 × 10 2 (CO) for the stone tripod stove during fodder preparation to 6.20 × 10 2 (PM2.5 ) and 2.22 × 10 3 (CO) for the traditional mud stove during liquor distillation. Usable PN data were only available for one house, during heating using a metal chimney stove, which presented an emission rate of 3.24 × 10 13 particles/min. Interventions to control household air pollution in Bhutan, in order to reduce the health risks associated with cooking and heating, are recommended.